C–H Bond Transformations Leading to the Synthesis of Organic Functional Materials - Kuninobu, Yoichiro; Sueki, Shunsuke (Synthesis, 2015)
In this review, transition-metal-catalyzed or -mediated C–H transformations leading to the synthesis of organic functional materials, such as oligomers, polymers, and π-conjugated molecules, are summarized.1 Introduction2 Oligomers and Polymers2.1 Synthesis of Oligomers and Polymers2.2 Chemical Modification of Polymers3 π-Conjugated Molecules3.1 Indenes and Fluorenes3.2 Acenes3.3 Triphenylenes3.4 Chemical Modification of Perylene Diimides3.5 Nanographenes3.6 Condensed Polycyclic π-Conjugated Molecules with Five-Membered Heteroaromatic Rings3.7 π-Conjugated Molecules with Nitrogen-Containing Six-Membered Heteroaromatics3.8 Porphyrins3.9 Miscellaneous (π-Conjugated Molecules)4 Miscellaneous (Excluding Polymers and π-Conjugated Molecules)5 Outlook and Conclusions
Keywords: catalyst; C–H activation; C–H functionalization; π-conjugated molecule; π-conjugation; functional material; oligomer; polymer